2010
DOI: 10.1097/scs.0b013e3181c3465e
|View full text |Cite
|
Sign up to set email alerts
|

Papilledema in Isolated Single-Suture Craniosynostosis

Abstract: The purpose of this retrospective study was to assess the prevalence of papilledema in patients with isolated craniosynostosis. Second, we wanted to assess if the presence of ventricular dilatation on computed tomography (CT) scan is a predictive factor for the occurrence of papilledema. We included 205 consecutive children with an isolated single-suture craniosynostosis, who had at least 1 fundus examination. Preoperative CT scans of the brain were examined for the presence of ventricular dilatation.Papillede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 16 publications
2
34
0
2
Order By: Relevance
“…It is well documented, that a subset of non-syndromic suture fusion patients show an elevated intracranial pressure (ICP) with a potential negative impact on brain development (Florisson et al, 2010). However, the exact relationship between ICP, intracranial volume and impaired brain development remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented, that a subset of non-syndromic suture fusion patients show an elevated intracranial pressure (ICP) with a potential negative impact on brain development (Florisson et al, 2010). However, the exact relationship between ICP, intracranial volume and impaired brain development remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent retrospective study on the prevalence of papilledema in 205 patients with single suture craniosynostosis, papilledema was noted in 9.7 % of sagittal suture synostosis, 5.6 % in the metopic suture group and no papilledema seen in patients with coronal or lambdoidal suture synostosis [7]. This study highlights the importance of optic nerve assessments in single suture craniosynostosis.…”
Section: Optic Neuropathymentioning
confidence: 83%
“…The majority of articles are retrospective case series with a small number of patients, limited follow-up, and varying quantitative and qualitative descriptions of ocular findings. Furthermore, data on ocular findings are often limited, and longitudinal follow-up of patients before and after craniofacial repair is often not reported [7].…”
Section: Introductionmentioning
confidence: 98%
“…Renier et al reported an increased ICP in 14% in scaphocephaly (Renier et al, 2000). Florisson et al reported about a prevalence of papilloedema in scaphocephaly of 9.7% (Florisson et al, 2010) and Taylor et al found a relationship between abnormalities of venous drainage and increased ICP in children with syndromic craniosynostosis (Taylor et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…Increased ICP can be identified clinically by fundus examination as papilloedema or optic atrophy (Florisson et al, 2010). The prevalence of elevated ICP in nonsyndromic craniosynostosis differs according to the affected suture.…”
Section: Discussionmentioning
confidence: 99%